Pemakaian Teknik Pendinginan Pasif Dalam Mitigasi Urban Heat Island (UHI): Tinjauan Literatur - Angkasa, Zuber; Angrini, Sisca Novia; Febrina, Sandra Eka; Iskandar, Iskandar (Arsir, 2023)
Sustainable development has become a significant issue nowadays. The passive cooling technique is used instead of the active cooling technique for less operation energy consumption. Previous research has identified urban heat island (UHI) phenomena in big cities because of climate change. Efforts have been made to reduce and mitigate this phenomenon, and the passive cooling technique is one of the efforts that count off. A comprehensive literature review has yet to highlight passive cooling techniques to overcome UHI. This paper will systematically review research on passive cooling techniques as UHI mitigation. The result indicates the pros and cons of various passive cooling techniques considering every previously identified factor that will help every stakeholder to reduce and mitigate UHI using passive cooling techniques.